2008
DOI: 10.1007/s00253-008-1517-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification, biochemical and molecular characterization of a metalloprotease from Pseudomonas aeruginosa MN7 grown on shrimp wastes

Abstract: A protease-producing bacterium was isolated and identified as Pseudomonas aeruginosa MN7. The strain was found to produce proteases when it was grown in media containing only shrimp waste powder (SWP), indicating that it can obtain its carbon, nitrogen, and salts requirements directly from shrimp waste. The use of 60 g/l SWP resulted in a high protease production. Elastase, the major protease produced by P. aeruginosa MN7, was purified from the culture supernatant to homogeneity using acetone precipitation, Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The rich and diverse composition of food wastes-which includes proteins, starch, insoluble carbohydrates, and lipids-can facilitate the production of a diverse range of enzymes. Some characteristic categories of enzymes that have already been produced from food wastes are amylases [23,24], proteases [25,26], ligninocellulolytic enzymes [27,28], lipases [29,30], and pectinolytic enzymes [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The rich and diverse composition of food wastes-which includes proteins, starch, insoluble carbohydrates, and lipids-can facilitate the production of a diverse range of enzymes. Some characteristic categories of enzymes that have already been produced from food wastes are amylases [23,24], proteases [25,26], ligninocellulolytic enzymes [27,28], lipases [29,30], and pectinolytic enzymes [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Proteases producing bacteria are widely isolated from soil with high protein content (Sing et al, 2001). Genus Pseudomonas a gram-negative bacterium that predominantly produces alkaline proteolytic enzymes and the proteases has been purified (Jellouli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PCR with the primer pair ME4F/ME4R yielded a 1,988 bp fragment carrying a 1,497 bp ORF encoding a polypeptide composed of 498 amino acid residues (AB618054). The N-terminal amino acid residue of mature ME-4 protease (Cheng et al 2009) is located at position 198 of the deduced amino acid sequence, which suggested that ME-4 protease is synthesized as a pre-pro-protein, as previously observed for elastases from P. aeruginosa (Schad et al 1987;Jellouli et al 2008). The sequence of the first 20 N-terminal residues of the 197 amino acid pre-pro-region was similar to the signal peptide sequences of Pseudomonas elastases (BAB79621, AAG07111, and AAZ78231), and was followed by a 177 amino acid pro-peptide (Bever and Iglewski 1998;Gupta et al 2008).…”
Section: Resultsmentioning
confidence: 70%
“…The probe hybridized to 3.2 kb PstI, 5.0-kb EcoRI, and 6.0 kb ClaI fragments (data not shown), which indicated that strain ME-4 carries one gene encoding pre-pro-LasB_ME4. These findings indicate that native ME-4 protease might be identical to one of the Pseudomonas elastases (Gupta et al 2008;Jellouli . 2008).…”
Section: Resultsmentioning
confidence: 90%